دراسة سلوك نماذج من المداخن البيتونية المسلحة الصناعية المحلية تحت تأثير الأحمال الزلزالية باستخدام التحليل بالسجلات الزمنية الصنعية (Latakia University Journal -Engineering Sciences Series, 2019)
The reinforced concrete chimneys are used as a vertical channel through which the gases of the combustion products in the plants and stations are discharged into the air to reduce air pollution. one of the most important applications in power plants and petrochemical Factories, They can be classified according to construction materials to: concrete , metal or brick . In the longitudinal section it can be conical (fully tapered chimney) , cylindrical chimneys or Partially Tapered Chimney (conical - cylindrical) . The chimney is lined from the inside by a layer of bricks, which helps protect the chimney shell from the high heat of the exhaust gases . The Syrian coast is classified as a seismically active zone , The Peak Ground acceleration is PGA = 0.3"0.4g and it is exposed to high Wind speeds . Where the speed of one wind blowing  for an average of twenty seconds (Vk) 42-44 m / sec . The chimneys  are very sensitive to the effects of wind because of their length and their large slenderness . And therefore must resist the effect  of earthquakes and wind loads together The purpose of this study is to study the behavior of three models of chimneys with equal height (110m) and a different  longitudinal section : conical (fully tapered chimney) , cylindrical and Partially Tapered Chimney (conical-cylindrical) by using the synthetic time histories analysis through the case of a study using the synthetic time histories analysis by conducting an applied analytical study on a 3D model of the chimneys, were used for real earthquakes that were scaling by using the time domain and the frequency domain to suit the Syrian response spectrum.   تستخدم المداخن البيتونية المسلحة كقناة رأسية يُمر بها غازات هي نواتج الاحتراق في المصانع والمحطات لتطردها في الهواء الجوي، وذلك للتخفيف من التلوث الهوائي، ومن أهم تطبيقاتها في محطات الطاقة والمصانع البتروكيميائية، يمكن تصنيفها تبعا لمواد الإنشاء إلى: بيتونية ، معدنية أو قرميدية، وفي المقطع الطولي يمكن أن تكون مداخن مخروطية أو أسطوانية أو بمقطع مختلط (جذع مخروط وأسطوانية)، يتم تبطين المدخنة من الداخل بطبقة من الأجر القرميدي وهو يفيد في حماية جدار المدخنة البيتوني من الحرارة المرتفعة لغازات العوادم. يصنف الساحل السوري على أنه منطقة نشطة زلزالياً حيث يبلغ التسارع الأرضي الأعظمي PGA= 0.3-0.4g, كما أنه يتعرض لرياح وبسرعات عالية، حيث تبلغ سرعة الهبة الواحدة لمتوسط عشرين ثانية (Vk)42-44 m/sec، وبما أن منشآت المداخن حساسة جداً تجاه تأثيرات الرياح بسبب طولها ونسبة نحافتها الكبيرة. فإن المفترض أن تصمد حيال تأثير حمولات الزلازل والرياح. يهدف هذا البحث إلى دراسة سلوك ثلاثة نماذج من المداخن بارتفاعات متساوية m 110 وبمقطع طولي مختلف: مخروطية، أسطوانية ومقطع طولي مختلط (مخروطي – أسطواني) باستخدام التحليل بالسجلات الزمنية الصنعية، وذلك بإجراء دراسة تحليلية تطبيقية على نماذج فراغية(3D)  للمداخن حيث استخدمت سجلات زمنية لزلازل حقيقية تم تقييسها باستخدام طريقتي مجال الزمن ومجال التردد لتلائم طيف الاستجابة للكود العربي السوري.